An evaluation of the process of strategic management in urban councils in Zimbabwe - Chinongwa, Edward; Marima, Nelia Eta (Indonesian Journal Of Business And Economics, 2023)
The study sought to evaluate the process of strategic management in urban councils in Zimbabwe. This was in response to notable failure in service delivery by these key institutions in the country. A quantitative research approach was used in the study with a population of 3031. Using a cluster sampling technique, a sample size of 341 professional employees was drawn, using the Krejcie Morgan sample size determination table. Data was collected using a questionnaire after having been pilot-tested.  and the reliability was tested through internal consistency, where Cronbach’s Alpha coefficient of above 0.7 confirmed the reliability of the research instrument. Data analysis was done using an SPSS version 23. Descriptive statistical techniques which include mean, standard deviation, frequency, and percentages were used in the analysis of data. The elements of the strategic management process which are strategic intent, strategy formulation, and strategy implementation were used as variables for evaluation. The findings of the study revealed poor compliance with the process of strategic management by urban councils in Zimbabwe. The results indicate a lack of strategic management practice in urban councils in Zimbabwe thus confirming their notable poor performance in terms of service delivery. It is therefore recommended that in practicing strategic management, urban councils in Zimbabwe comply with its process for enhanced performance.   Keywords: strategic intent; strategic management practice; strategic management process; strategy formulation; strategy implementation